Adolescencia y ritos de transición : una articulación del psicoanálisis postfreudiano y lacaniano (2011)
ABSTRACT: The article is intended to perform an articulation of the theoretical developments on adolescence by postfreudianos, psychoanalytic authors such as e. Erickson and Lacanian, as j. Ubieto. This with the intention of showing that despite the theoretical and conceptual differences between authors is possible to establish a dialogue between these approaches, which can serve not only the psychoanalysts but also psychologists and professionals in the social sciences. The article shows that the theoretical developments of these authors are supported by the linkage of psychoanalysis with scientific disciplines such as psychology, sociology, among others. The article highlights the fact that to study teenage perspective Psychoanalytical is essential to analyze the phenomenon of the rites of passage or transition from childhood to adulthood, since both antiquity and modernity such rites are allowing to build the identity of adult and thereby promote or inder entry into social.